Lignin pretreatment of oil palm empty fruit bunch using ligninolytic enzyme-mediator and cellulose hydrolysis for fermentable sugar production - Zanirun, Zuraidah (2016)
Lignocellulosic biomass is the source of cellulosic materials which leads to the fermentable sugars productions. The position of Malaysia as among the top producers and major exporter of palm oil generates abundant of palm oil biomass particularly oil palm empty fruit bunch (OPEFB). Conversion to value added products of such organic acid, compost, bioenergy and enzymes besides sugars which is the key step for most of the processes may overcome the issues in future wastes management.Locally isolated fungus namely Pycnoporus sanguineus was found to be the best ligninolytic enzyme producer among the 20 fungi screened on dyed agar plate.Decolorization of Remazol Brilliant Blue dye added to agar media by the fungi showed the ability to secrete ligninolytic enzyme and further profiling resulted in the production of laccase as the major enzyme followed by manganese peroxidase and lignin peroxidase with the least activities.Physical and chemical structural and compositional particularly lignin acts as a barrier to the enzymatic hydrolysis of cellulose. Appropriate pretreatment to remove lignin is necessary to ensure the access of cellulases enzyme to the cellulosic material embedded in the lignocellulosic matrix. In this study, the application of crude ligninolytic enzyme extracts alone from locally isolated fungi namely Pycnoporus sanguineus to the oil palm empty fruit bunch as a biological pre-treatment was able to produce 19 g/L of fermentable sugars during enzymatic hydrolysis using commercial cellulase and was increased up to approximately 30 g/L with the addition of combination mediator of HBT-Mn (II) and ABTS-Mn (II). Based on Klason lignin determination, the highest lignin removal was achieved at the concentration of 1.5% HBT, 4 mM ABTS and 2 mM manganese ion as much as 8.02%, 8.68% and 3.7%, respectively as compared to raw OPEFB. Klason lignin was also removed by as much as 8.8% at 50°C and 8.16% at 10% of substrate loading. Supported results on the FTIR and GC-MS analysis showed the changes in the structure and chemical bonds of the Cellulase is the key enzyme for the cellulose hydrolysis producing fermentable sugars. The effect of cultivation condition of two locally isolated ascomycetes strains namely Trichoderma asperellum UPM1 and Aspergillus fumigatus UPM2 were compared in submerged and solid state fermentation. Physical evaluation on water absorption index, solubility index and chemical properties of lignin, hemicellulose and cellulose content as well as the cellulose structure on crystallinity and amorphous region of treated oil palm empty fruit bunch (OPEFB) (resulted in partial removal of lignin), sago pith residues (SPR) and oil palm decanter cake (OPDC) towards cellulases production were determined. Submerged fermentation shown significant cellulases production for both strains in all types of substrates. Crystallinity of cellulose and its chemical composition mainly holocellulose components was found to significantly affected the total cellulase synthesis in submerged fermentation as the higher crystallinity index and holocellulose composition will increase cellulase production. Treated OPEFB was apparently induced the total cellulases from Trichoderma asperellum UPM1 and Aspergillus fumigatus UPM2 with 0.66 U/mg FPase, 53.79 U/mg CMCase, 0.92 U/mg β-glucosidase and 0.67 U/mg FPase, 47.56 U/mg and 0.14 U/mg β-glucosidase,respectively. Physical properties of water absorption and solubility for OPEFB and SPR also had shown significant correlation on the cellulases production.The competency of crude cellulase cocktail from both isolates of Trichoderma asperellum UPM1 and Aspergillus fumigatus UPM2 were mixed at 3:2 ratio and applied on the enzymatically treated OPEFB from local isolate were compared with the commercial cellulase and the result obtained was 30% cellulose hydrolysis percentage for ligninolytic-mediator pretreatment and 44% using commercial cellulase. Regardless of the lower individual cellulase from local isolates compared to commercial cellulase.It is therefore suggested that biological approaches alone using ligninolytic enzymemediator as pretreatment and cellulase enzymes produced locally had a promising potential for fermentable sugar productions for OPEFB.